The complexity of tau in Alzheimer's disease. (13th July 2019) - Naseri, Nima N.; Wang, Hong; Guo, Jennifer; Sharma, Manu; Luo, Wenjie
Highlights: Pathogenic tau species disrupt synaptic functions at the pre-and-post-synapse. Acetylation has emerged as a novel pathological modification of tau. Seeding and spreading of tau aggregates is associated with distinct pathological strain specificity and via various mechanisms. Tau pathology is associated with glia activation in a highly interactive manner. 3D cultures and brain organoids provide new platforms for exploring the role of tau in Alzheimer's disease. Abstract: Alzheimer's disease (AD) is characterized by two major pathological lesions in the brain, amyloid plaques and neurofibrillary tangles (NFTs) composed mainly of amyloid-β (Aβ) peptides and hyperphosphorylated tau, respectively. Although accumulation of toxic Aβ species in the brain has been proposed as one of the important early events in AD, continued lack of success of clinical trials based on Aβ-targeting drugs has triggered the field to seek out alternative disease mechanisms and related therapeutic strategies. One of the new approaches is to uncover novel roles of pathological tau during disease progression. This review will primarily focus on recent advances in understanding the contributions of tau to AD.